(untitled) (REMUNOM, 2026)
The article analyzes the constitution of experiences of belonging, collective identity, and spirituality within shared cultural and ritual practices, using manifestations such as football and the Círio de Nazaré as empirical references, understood as symbolic spaces for the production of meaning. It starts from the conception that spirituality is not restricted to formal religious contexts but can emerge in intense collective practices permeated by affective bonds, shared narratives, and experiences of symbolic communion. It draws from Adam (2012) the understanding that experiences of meaning and transcendence manifest in daily life and secular contexts, especially when articulated with forms of collective belonging. The relational dimension of spirituality is understood through Boff (2001), for whom the spiritual experience is expressed in the bond with the other, in care, and in ethical responsibility, overcoming individualistic and intimist conceptions. Complementarily, Turner (1969) contributes by introducing the concept of liminality, highlighting rituals as moments of provisional suspension of social hierarchies, in which bonds, affections, and feelings of communion are intensified. Assmann (2011) highlights that cultural memory constitutes a field of disputes, selections, and resignifications, in which traditions are continuously reinterpreted by new generations. In the field of football, Toledo (2002) demonstrates that the act of supporting a team goes beyond the sporting event, configuring itself as a social practice of belonging, identity, and collective memory. Thus, the study argues that football and popular religiosity, far from being antagonistic universes, operate as symbolic devices that produce meaning, identity, and experiences of transcendence in everyday life, revealing the centrality of collective practices in the construction of contemporary social life.